Biomass-derived flexible porous carbon materials and their applications in supercapacitor and gas adsorption. (5th September 2017) - Xiao, Pei-Wen; Meng, Qinghai; Zhao, Li; Li, Jing-Jing; Wei, Zhixiang; Han, Bao-Hang
Abstract: In this work, biomass-related fabrics (cotton, cotton–flax, and flax fabrics) were used as precursors to synthesize a series of flexible porous carbon materials through simple carbonization at different temperatures. The porosities of these materials were then studied in detail. Physicochemical and texture properties, such as morphology, elemental composition, degree of structural order, and functional group, were also comprehensively characterized to supply basic information with regard to the utilization of these materials. Furthermore, flexible heteroatom-doped porous carbon materials were obtained through a "dipping and drying" process. Given that these biomass-derived carbon materials are flexible and porous, the applications of these materials as flexible and free-standing electrodes in supercapacitors and gas adsorbents were investigated. Graphical abstract: Highlights: Biomass-related fabrics (cotton, cotton–flax, and flax fabrics) were used as precursors to synthesize a series of flexible porous carbon materials through carbonization at different temperatures. The physicochemical and texture properties of the materials are reported. By using a "dipping and drying" method, flexible heteroatom-doped porous carbon materials were obtained. The Brunauer–Emmett–Teller specific surface area values of the obtained materials are 310–650 m 2  g −1 . These biomass-derived flexible carbon materials exhibit good performance as gas adsorbents and flexible free-standing electrodes in supercapacitors.